Determination of Mu'nah Pawn from The Perspective of Fatwa DSN MUI (Comparative Study on Pegadaian Syariah and Bank Syariah Indonesia) - Anam, Khoiril; Musadad, Ahmad; Kumala DS, Agustina (Et-Tijarie, 2024)
The determination of mu'nah on Pegadaian Syariah and Bank Syariah Indonesia must be in accordance with the provisions of the DSN MUI Fatwa related to rahn. However, in practice, there are often problems because in the process of determining mu'nah it does not refer to the estimated amount of goods mortgaged (marhûn bih) but based on the estimated value of gold. This provision has a risk that harms consumers in financing contracts through pawns because there is a potential error in the assessment of the value of gold or because the accuracy of the assessment is low. This paper examines the mechanism and suitability of the determination of mu'nah at Pegadaian Syariah and Bank Syariah Indonesia in Bangkalan from the perspective of DSN-MUI fatwa.The research method used is a qualitative method with descriptive-analytical analysis techniques. The source of data was obtained through observation and interviews with informants, namely employees of Pegadaian Syariah and BSI in Bangkalan as well as documentation of the source of documents related to the determination of mu'nah.The results of the study show that the determination of mu'nah (maintenance costs) of pawns at Pegadaian Syariah and Bank Syariah Indonesia is determined based on the estimated value, not the amount of the loan. The determination of mu'nah is in accordance with the conditions and pillars of pawn, namely âqid, where râhin and murtahin have the legal skills to carry out pawn practice, then there is clarity and agreement from the râhin and murtahin, collateral can be sold and has a value equivalent to the amount of debt. The agreement/contract used does not contain an element of usury, as evidenced in gold pawn financing activities, does not apply an interest system in obtaining profits, but from the cost of maintaining pawn goods and does not contain an element of gharar, as evidenced in this gold pawn financing, the object of financing is clear both in terms of quantity, quality, and price of goods.